Fatigue Safety Coefficients for Ultra – High Region of Load Cycles - Daniel Varecha; Slavomir Hrcek; Otakar Bokuvka; Frantisek Novy; Libor Trsko; Ruzica Nikolic; Michal Jambor (Communications - Scientific letters of the University of Zilina, 2020)
In this paper the authors introduce results from the field of the fatigue safety of selected steels in the region of ultra - high number of loading cycles. The fatigue tests were carried out at high frequency tension - compression loading (f = 20 kHz, T = 20 ± 5°, R = -1) in the region from N = 106 to N = 109 cycles. The fatigue safety coefficients were calculated by four methods (Goodman, Gerber, ASME elliptic and Soderberg). The percentage reduction of the fatigue safety coefficients (N = 109 vs. N = 106 cycles) was at Goodman, 7.99 ÷ 10.83 %, Gerber, 5.27 ÷ 8.26 %, ASME, 1.89 ÷ 6.42 % and Soderberg, 6.51 ÷ 10.25 %.